Clinical sequencing using a next‐generation sequencing‐based multiplex gene assay in patients with advanced solid tumors. Issue 7 (22nd May 2017) - Kou, Tadayuki; Kanai, Masashi; Yamamoto, Yoshihiro; Kamada, Mayumi; Nakatsui, Masahiko; Sakuma, Tomohiro; Mochizuki, Hiroaki; Hiroshima, Akinori; Sugiyama, Aiko; Nakamura, Eijiro; Miyake, Hidehiko; Minamiguchi, Sachiko; et al.
Abstract : Advances in next‐generation sequencing (NGS) technologies have enabled physicians to test for genomic alterations in multiple cancer‐related genes at once in daily clinical practice. In April 2015, we introduced clinical sequencing using an NGS‐based multiplex gene assay (OncoPrime) certified by the Clinical Laboratory Improvement Amendment. This assay covers the entire coding regions of 215 genes and the rearrangement of 17 frequently rearranged genes with clinical relevance in human cancers. The principal indications for the assay were cancers of unknown primary site, rare tumors, and any solid tumors that were refractory to standard chemotherapy. A total of 85 patients underwent testing with multiplex gene assay between April 2015 and July 2016. The most common solid tumor types tested were pancreatic ( n = 19; 22.4%), followed by biliary tract ( n = 14; 16.5%), and tumors of unknown primary site ( n = 13; 15.3%). Samples from 80 patients (94.1%) were successfully sequenced. The median turnaround time was 40 days (range, 18–70 days). Potentially actionable mutations were identified in 69 of 80 patients (86.3%) and were most commonly found in TP53 (46.3%), KRAS (23.8%), APC (18.8%), STK11 (7.5%), and ATR (7.5%). Nine patients (13.0%) received a subsequent therapy based on the NGS assay results. Implementation of clinical sequencing using an NGS‐based multiplex gene assay was feasible in the clinical setting and identified potentially actionable mutations in more than 80% of patients. Current challenges are to incorporate this genomic information into better therapeutic decision making. Abstract : In April 2015, we introduced clinical sequencing using a next‐generation sequencing (NGS)‐based multiplex gene assay certified by the Clinical Laboratory Improvement Amendment into daily clinical practice. Implementation of clinical sequencing using an NGS‐based multiplex gene assay was feasible in the clinical setting and identified potentially actionable mutations in more than 80% of patients with advanced solid tumors. Current challenges are to incorporate this genomic information into better therapeutic decision making.